Pancreatobiliary diseases in a patient with spontaneous perforation of duodenal diverticulum: a case report - Terasoto, Lucas; Moreira, Paula Heroso; Faccio, Enzo Natanael; Veiga, Nicolas Fortunato; Costa, Giovana Rezende Fernandes; Nasr, Adonis (Brazilian Journal of Case Reports, 2024)
Duodenal diverticula are most found in the second portion of the duodenum. They may be associated with pancreatobiliary diseases, such as choledocholithiasis and acute pancreatitis, though the understanding of this relationship remains limited. Other complications, such as spontaneous perforation of these diverticula, are rare and severe, often requiring surgical intervention and carrying high morbidity and mortality rates. In this article, we review the literature on this topic and describe the case of a patient with biliary acute pancreatitis and choledocholithiasis associated with retroperitoneal air due to duodenal diverticulum perforation. The patient was managed with conservative treatment for the perforation and clinical management of the pancreatitis, followed by endoscopic treatment of the choledocholithiasis.